Conductive material for secondary battery electrodes having ion conductivity and binder affinity

The core-shell structured conductive material addresses uneven dispersion and interfacial resistance issues by ensuring stable ion transport and electron conduction, improving battery performance and energy density.

KR103044233B1Active Publication Date: 2026-11-05CHEONGJU UNIV IND & ACADEMY COOPERATION FOUND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250089322
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2026-11-05
Estimated Expiration
2045-07-03

AI Technical Summary

Technical Problem

Conventional conductive materials for secondary battery electrodes suffer from uneven dispersion due to low chemical and physical compatibility with binders, leading to high interfacial resistance, impaired ion transport, and reduced electrical and mechanical stability, which affects charge/discharge efficiency and energy density.

Method used

A conductive material with a core-shell structure, where the conductive core is coated with a shell material that has affinity with the binder and ion conductivity, enhancing dispersion stability and ion transport capability.

Benefits of technology

The core-shell structure improves electron and ion transport pathways, leading to enhanced charge/discharge performance, mechanical stability, and increased energy density by suppressing aggregation and increasing binder adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112025075206832-PAT00005_ABST
    Figure 112025075206832-PAT00005_ABST
Patent Text Reader

Abstract

The present invention relates to a conductive material for a secondary battery electrode comprising a conductive core and a shell formed on all or at least part of the surface of the core, having binder affinity and ion conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to conductive particles used as a conductive material for a secondary battery electrode. Background Technology

[0002] The electrode of a secondary battery is generally composed of an active material, a conductive material, and a binder, and among these, the conductive material plays a key role in ensuring the electrical conductivity of the electrode by forming electron conduction paths between active material particles. In conventional technology, carbon-based materials such as carbon black, carbon nanotubes (CNT), graphene, and carbon fibers have been mainly used as conductive materials. These conductive materials are mixed with a binder as an electrode slurry, coated onto a current collector, and then the electrode is manufactured through drying and rolling.

[0003] However, conventional conductive materials have various limitations. First, due to low chemical or physical compatibility between the conductive material and the binder, conductive particles are unevenly dispersed within the binder. This hinders the formation of an electron conduction network within the electrode and degrades not only electrical performance but also the mechanical stability of the electrode. Additionally, high resistance occurs at the interface between the conductive material and the binder, hindering smooth ion transfer. This reduces the charge / discharge rate and negatively affects output characteristics.

[0004] In addition, conventional conductive materials are often designed with a focus on electron conduction and are separated from the ion transport path, which results in a problem where ions or electrons are not effectively transported in some regions within the electrode, leading to reduced reaction efficiency. Furthermore, carbon-based conductive materials tend to aggregate easily due to their high surface energy, which impairs the dispersion stability of the slurry and hinders the uniformity of the slurry manufacturing and coating processes.

[0005] Furthermore, when attempting to increase electrode conductivity by increasing the content of the conductive material, a structural limitation arises in which the content of the active material is relatively reduced, resulting in a lower energy density of the battery. Although various technologies have been proposed to address these issues, most have focused on only one aspect—either the electronic conductivity or the dispersibility of the conductive material—there have been limitations in improving the overall performance of the electrode. Prior art literature

[0006] Korean Published Patent No. 10-2023-0007337 (Publication Date: 2023.01.12) Korean Published Patent No. 10-2008-0019533 (Publication Date: 2008.03.04) The problem to be solved

[0007] The technical problem that the present invention aims to solve is to provide a new conductive material for a secondary battery electrode that can resolve the issue of uneven dispersion of the conductive material within the electrode due to low chemical and physical compatibility between the conductive particles and the binder, and the reduction in charge / discharge efficiency caused by the failure to smoothly secure ion transport pathways due to high interfacial resistance on the surface of the conductive material. means of solving the problem

[0008] To achieve the above technical problem, the present invention provides a conductive material for a secondary battery electrode composed of conductive particles having a core-shell structure, wherein the conductive core is coated with a shell material having both affinity with a binder and ion conductivity.

[0009] A conductive material for a secondary battery electrode according to the present invention comprises a conductive core and a shell formed on all or at least part of the surface of the core, having binder affinity and ion conductivity, thereby enabling simultaneous securing of dispersion stability of conductive particles and ion transport capability within the electrode (see FIG. 2 and FIG. 3).

[0010] The conductive core of the conductive material according to the present invention may include one or more selected from the group consisting of carbon black, carbon nanotubes (CNT), graphene, carbon fibers, metal nanoparticles, and conductive metal compounds, as a component that directly influences the efficiency of forming electron transfer pathways within the electrode and the maintenance of electrical conductivity and leads the electron conductivity characteristics.

[0011] Carbon black is advantageous for forming conductive networks due to its nanoscale dispersibility and high specific surface area characteristics; however, since its bonding strength with the shell may be low, interface activation treatment may be performed in parallel. Carbon nanotubes (CNTs) can form one-dimensional conduction pathways, providing continuous electron passages within the electrode, and facilitate stable coating of the shell material through their high specific surface area structure. Graphene provides high mechanical strength and excellent electrical conductivity, and its planar structure is advantageous for ensuring dispersion stability within the slurry.

[0012] Metallic materials enable the formation of strong electron pathways based on very high electrical conductivity, which is particularly advantageous for electrodes for high-speed charging and discharging or high-power cells. For example, metal nanoparticles or nanowires such as silver (Ag), copper (Cu), and nickel (Ni) can be used.

[0013] Metal compound-based materials can simultaneously ensure electrical conductivity and thermal stability, and conductive metal oxides, nitrides, and carbides can be used as core materials.

[0014] Furthermore, the conductive core may be based on composite materials and can be implemented, for example, as a CNT-metal nanoparticle composite, a graphene-ceramic composite, or a carbon-metal oxide composite. The composite structure can simultaneously ensure interfacial stability, conductivity, dispersibility, and chemical durability, and can enhance the physical and chemical stability of the core-shell bond through various electrostatic and chemical interactions during shell coating.

[0015] The shell of the conductive material according to the present invention may be composed of various inorganic materials, organic materials, inorganic-organic composites, ionic liquid impregnated materials, etc., designed to simultaneously have ion conductivity and affinity with a binder.

[0016] Inorganic material-based shells generally possess high chemical and thermal stability, making them advantageous in high-temperature environments or under conditions requiring long lifespan. For example, materials such as alumina (Al2O3), zirconia (ZrO2), and titania (TiO2) can be formed on the surface of a conductive core using methods such as the sol-gel method or atomic layer deposition (ALD). These oxides enable stable dispersion within the electrode through hydrogen bonding with the binder or physical adsorption, while simultaneously serving as a protective layer that inhibits electrolyte decomposition or blocks side reactions.

[0017] The organic material-based shell can be made of an ion-conductive polymer. For example, polymers such as polyethylene oxide (PEO), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), polyacrylic acid (PAA), and polyionic liquid polymers improve the binder dispersion of the conductive material particles within the electrode.

[0018] Shells based on inorganic-organic composites can be composed of inorganic ceramics and organic polymers in the form of nanocomposites, or in a multilayer or gradient structure, such as TiO2-PEO composites or systems of aluminum fluoride (AlF3) and ionic liquid coexistence. These composite structures can be implemented by placing an inorganic layer as an inner layer to increase bonding strength with the core, and applying an organic polymer layer as an outer layer to optimize interaction with the binder.

[0019] Furthermore, the shell may include a polymer doped with a lithium salt (LiTFSI, LiFSI, etc.), an ionic liquid or solid electrolyte, or an ion exchange resin-based material. These materials maximize the ion exchange efficiency at the electrode interface by supplying high-concentration ion carriers and are particularly effective in securing lithium ion transport pathways under high temperature or high current conditions. Additionally, they contribute to maintaining a stable interface by possessing high chemical stability with respect to the electrolyte.

[0020] In addition, the shell may be composed not only of a single layer but also of a multilayer structure, a gradient structure, a porous shell, etc.

[0021] A single-layer shell structure is a shell composed of a single material or a uniform composition, offering the advantages of relatively simple manufacturing and ease of achieving uniform coating quality. For example, it can be composed of ion-conducting polymers (PEO, PVDF-HFP, etc.) or inorganic oxides (TiO2, Al2O3), and performs the role of an ion diffusion pathway or an enhancer of interaction with binders independently.

[0022] A multilayer shell structure is composed of multiple material layers having different physicochemical properties stacked in succession. For example, there is a method in which the inner shell is composed of a ceramic material with high ion conductivity, and the outer shell is formed of an organic polymer with excellent physicochemical bonding strength with a binder. For instance, by depositing a metal oxide such as titania (TiO2) as an inner layer on a carbon-based core such as a carbon nanotube (CNT), and then forming a PEO-LiTFSI composite as an outer layer, it is possible to secure electronic and ion conductivity, interfacial stability, and binder affinity.

[0023] A gradient shell structure is a structure designed such that the composition or physical properties (ionic conductivity, density, etc.) change continuously from the inside to the outside of the shell. For example, the composition can be controlled such that the inside is formed with a high ionic conductivity ceramic composition and the content of organic polymers increases towards the outside, thereby gradually increasing binder affinity. Such compositional changes can reduce electrochemical instability caused by abrupt interfacial discontinuities and improve the structural flexibility and impact resistance of the entire shell.

[0024] A porous shell structure is designed to have micropores within or throughout the shell, which can significantly enhance the ion permeability of the shell itself.

[0025] Meanwhile, the above shell preferably has a thickness of 1 nm to 300 nm, taking into account ion conductivity, interfacial stability, and binder bonding strength. If the thickness of the shell is less than 1 nm, it is difficult to secure physical durability or adhesion with the binder, and if the thickness exceeds 300 nm, the shell becomes excessively thick, which may cause the electron conduction path within the electrode to be severed or the internal resistance to increase, thereby degrading the output characteristics of the battery, which is undesirable.

[0026] The conductive material for a secondary battery electrode according to the present invention can be implemented through various manufacturing processes, and a suitable manufacturing method can be selected depending on the composition, structure, thickness, interface characteristics, etc. of the shell. The process of forming a shell on the surface of prepared core particles is broadly classified into wet coating methods, dry coating methods, mechanochemical methods, heat treatment-based methods, and combinations thereof, and each process has various advantages and optimization conditions depending on the purpose.

[0027] In performing a process of preparing conductive core particles and coating a shell onto the surface of the core particles, wet coating processes such as sol-gel reactions, co-precipitation, and solution adsorption methods may be used, while dry methods such as Atomic Layer Deposition (ALD), Chemical Vapor Deposition (CVD), and Physical Vapor Deposition (PVD) can be utilized. Additionally, physical mixing and coating can be achieved through mechanochemical methods such as high-energy ball milling or mechanical alloying processes. Furthermore, in-situ polymerization, self-assembly methods, and composite processes can be applied without limitation.

[0028] Since the conductive material for a secondary battery electrode composed of core-shell structured conductive particles according to the present invention allows for customized design based on the purpose of use, electrode type, operating conditions, etc. of the battery, the composition of the shell material, the type of core, the shell structure, and the manufacturing process can be selectively combined according to the required characteristics for each application field. Through this, it is possible to realize a high-performance secondary battery that satisfies various target performance characteristics such as high power output, high energy density, long lifespan, and high stability. Effects of the invention

[0029] A conductive material for a secondary battery electrode composed of core-shell structured conductive particles according to the present invention comprises a conductive core and a shell having binder affinity and ion conductivity, thereby enabling the simultaneous formation of electron and ion transport pathways within the electrode, which improves high-rate charge / discharge performance and output characteristics. Furthermore, by improving the dispersion stability and interfacial adhesion of the shell, the aggregation of the conductive material is suppressed and the bonding strength with the binder is increased, thereby improving the mechanical stability and cycle life of the electrode. Additionally, the conductive material content can be reduced under the same internal resistance conditions, allowing for increased energy density. Consequently, it can be usefully applied to next-generation secondary batteries requiring high output, high energy density, and long lifespan characteristics. Brief explanation of the drawing

[0030] FIG. 1 is a schematic diagram illustrating a conventional conductive particle structure unevenly dispersed within a binder according to the prior art, showing a state in which conductive particles (2) are unevenly distributed within the binder (1) and conductive channels are formed inefficiently. FIG. 2 is a schematic diagram illustrating a core-shell structured conductive particle according to the present invention, showing a conductive particle (4) in which a shell (3) surrounding a conductive core (2) has both miscibility with a binder and ion conductivity, and an arrow indicates lithium ions (Li) even around the core through the shell. + Indicates that ) can move. FIG. 3 is a schematic diagram illustrating a state in which conductive particles of a core-shell structure according to the present invention are uniformly dispersed within a binder, and each conductive particle (4) is completely covered with a shell structure, thereby showing structural features that improve bonding strength with the binder (1) and form a uniform conductive network. Specific details for implementing the invention

[0031] In describing the present invention, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0032] Since embodiments according to the concept of the present invention may be subject to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in this specification or application. However, this is not intended to limit embodiments according to the concept of the present invention to specific disclosed forms, and it should be understood that they include all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention.

[0033] The terms used herein are merely for describing specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as “comprising” or “having” are intended to specify the existence of the described features, numbers, steps, actions, components, parts, or combinations thereof, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0034] The present invention will be described in more detail below with reference to examples.

[0035] The embodiments according to this specification may be modified in various different forms, and the scope of this specification is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more fully explain this specification to those with average knowledge in the art.

[0036] <Example> CNT Core / TiO 2- Fabrication of PEO-LiTFSI Multilayer Shell Conductive Particles and Cathode Application Effects

[0037] 1. Core and Shell Material Composition

[0038] As shown in Table 1 below, in this embodiment, a multi-walled carbon nanotube (MWCNT) is used as the core, and the shell formed on the surface of the core is formed as a double structure consisting of a primary shell having ion permeability and a secondary shell having binder affinity. The primary shell consists of an amorphous TiO2 film formed through a sol-gel process in which Ti(O-iPr)4 and water are reacted in a 1:2 molar ratio, and the secondary shell is formed by applying a slurry obtained by dispersing a CNT / TiO2 composite in a solution of polyethylene oxide (PEO) mixed with a lithium salt (LiTFSI) (EO:Li = 20:1). To induce interfacial bonding between the CNT core and the TiO₂ film, the silane coupling agent KH560 (γ-GPTMS, 1 wt% of CNT) was used, and the solvent used was a mixture of N-methylpyrrolidone (NMP) and isopropyl alcohol (IPA) in a volume ratio of 7:3.

[0039] [Table 1]

[0040]

[0041] 2. Preparation of Core-Shell Particles

[0042] First, 20 g of CNT was reacted in 5 M HNO3 at 80 °C for 2 hours, then washed with deionized water and dried. Subsequently, the surface of the CNT core was activated by treating it in a 1 wt% KH560 solution at 60 °C for 1 hour. Next, to form the primary shell (inner layer), the activated CNT was dispersed in a 45 wt% Ti(O-iPr) solution, the pH was adjusted to 2, and the mixture was stirred at 40 °C for 3 hours. Afterward, the CNT surface was heat-treated under vacuum at 150 °C for 30 minutes to form an amorphous TiO₂ film approximately 10 nm thick. The secondary shell (outer layer) was prepared by dispersing the CNT / TiO₂ composite in a 3 wt% PEO-LiTFSI solution to form a slurry, then dropwise drying. A solvent was evaporated at 90 ℃, and heat treatment was performed in a vacuum at 120 ℃ for 1 hour to form an outer layer of about 30 thickness forming a crystalline lithium ion channel on a TiO₂ film.

[0043] 3. Electrode Manufacturing and Cell Assembly

[0044] As an example, a battery (CNT-CS) containing a core-shell structured conductive material prepared above and as a comparative example, a battery (CNT) containing CNT as a conductive material were prepared according to the conditions shown in Table 2 below. A coin cell was prepared using an electrode prepared by coating a slurry, prepared by mixing each conductive material with an active material (Si / C) and a binder, onto a copper foil current collector, and 1 M LiPF6 / EC:DEC.

[0045] [Table 2]

[0046]

[0047] 4. Evaluation of Electrochemical Performance and Dispersion Stability

[0048] The results of the electrochemical characterization of the batteries prepared above are summarized in Table 3 below. Although the electron conductivity within the electrode of the example was 22 S / cm, which was 8% lower than that of the comparative example (24 S / cm), the ionic conductivity was 4.9 × 10⁻⁶ at 25 ℃. -6 Measured in S / cm, comparison sample (7.1 × 10⁻⁶ -7 It improved by approximately 6.9 times compared to S / cm. In the high-rate characteristic evaluation, the example showed a capacity retention rate of 88% under 2C discharge conditions, while the comparative example was confirmed to be 71%. In terms of long-term lifespan, after 300 cycles at 0.5C, the example maintained 92% of its capacity, while the comparative example maintained 79%, showing a difference of approximately 17%. Same internal resistance (50 Ω·cm 2 According to the results of comparing the amount of conductive material used based on the achievement of ) the example was found to be able to reduce the amount of conductive material used by about 25% compared to the comparative example, thereby enabling an improvement in energy density.

[0049] [Table 3]

[0050]

[0051] Additionally, in the example, the slurry viscosity was reduced by about 15% through hydrogen bonding between the PVDF-HFP binder and the -OH / Si-OM, and the peel strength was 0.68 N / cm, which was significantly improved compared to the comparative example (0.42 N / cm). Furthermore, according to the dispersion stability evaluation results (based on Turbiscan TSI), the TSI value of the example was 0.09 (24h), which is lower than that of the comparative example (0.55), confirming that aggregation is suppressed and contributes to the formation of a uniform electrically conductive network.

[0052] The present invention is not limited to the above embodiments and can be manufactured in various different forms, and those skilled in the art will understand that the invention can be implemented in other specific forms without changing the technical concept or essential features of the invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.

Claims

Claim 1 A conductive material for a secondary battery electrode comprising: a conductive core; and a shell formed on all or at least part of the surface of the core and having binder affinity and ion conductivity. Claim 2 A conductive material for a secondary battery electrode according to claim 1, wherein the conductive core comprises one or more selected from the group consisting of carbon black, carbon nanotubes, graphene, carbon fibers, metal nanoparticles, and conductive metal compounds. Claim 3 A conductive material for a secondary battery electrode according to claim 1, characterized in that the shell has a thickness of 1 to 300 nm. Claim 4 A conductive material for a secondary battery electrode according to claim 1, wherein the shell comprises one or more selected from the group consisting of metal oxides, metal fluorides, lithium ion conductive ceramics, ion conductive polymers, inorganic-organic hybrid materials, or ionic liquid impregnated materials. Claim 5 A conductive material for a secondary battery electrode according to claim 1, wherein the shell comprises: an inner layer having ion conductivity; and an outer layer having affinity with a binder. Claim 6 A conductive material for a secondary battery electrode according to claim 5, comprising: a core made of carbon nanotubes (CNT); an inner layer made of titanium dioxide (TiO2) formed on the surface of the core; and an outer layer made of a polymer composite comprising polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) formed on the surface of the inner layer. Claim 7 A secondary battery having an electrode comprising a conductive material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • An anode for all-solid type batteries including solid electrolyte

    KR1020190044397A

  • Electrode composite conducting agent for lithium battery, electrode for lithium battery, preparing method thereof, and lithium battery including the same

    KR1020200058644A

  • Composite particles for electrochemical devices and a method for producing the same, a binder composition for a functional layer of an electrochemical device and a method for producing the same, a conductive paste for an electrode composite layer and a method for producing the same, a slurry for an electrode composite layer, an electrode for an electrochemical device, and an electrochemical device

    KR1020220027846A